2017
DOI: 10.1038/nm.4340
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1+ monocytes modulate learning and learning-dependent dendritic spine remodeling via TNF-α

Abstract: Impaired learning and cognitive function often occurs during systemic infection or inflammation. Although activation of the innate immune system has been linked to the behavioral and cognitive effects that are associated with infection, the underlying mechanisms remain poorly understood. Here we mimicked viral immune activation with poly(I:C), a synthetic analog of double-stranded RNA, and longitudinally imaged postsynaptic dendritic spines of layer V pyramidal neurons in the mouse primary motor cortex using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 64 publications
2
102
0
Order By: Relevance
“…This dichotomy also rules out a general impact of irradiation on cognitive tasks when assessed more than 8 weeks post reconstitution. Of note, other publications in the field have employed this approach to dissect the impact of radioresistant versus radiosensitive immune cells on learning (22,52).…”
Section: Discussionmentioning
confidence: 99%
“…This dichotomy also rules out a general impact of irradiation on cognitive tasks when assessed more than 8 weeks post reconstitution. Of note, other publications in the field have employed this approach to dissect the impact of radioresistant versus radiosensitive immune cells on learning (22,52).…”
Section: Discussionmentioning
confidence: 99%
“…The specific role of microglia can be investigated using microglial depletion models [22][23][24][25][26][27][28][29][30][31][32]. Most studies on microglial depletion employ pharmacological strategies involving the colony-stimulating factor 1 receptor (CSF1R), including PLX33397 or PLX5622 [33].…”
Section: Introductionmentioning
confidence: 99%
“…cortex, one of the brain regions involved in social behavior 39,40 , using transcranial two-photon microscopy 41 . We found that Mecp2 308/Y mice with neurological dysfunction and social behavioral deficits exhibited increased dendritic spine elimination ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…P2X7R-mediated IL-1β release may potentiate other inflammatory pathways. For example, peripherally generated TNFα has been shown to be involved in cortical synaptic remodeling 41,62 and is released upon activation of P2X7Rs 63 . Meningeal inflammation may prime IFNγmediated immune responses which have been associated with interneuron dysfunction and social deficits 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation